Prompt Antiviral Action of Pulmonary CD8+ TRM Cells Is Mediated by Rapid IFN-γ Induction and Its Downstream ISGs in the Lung - Jiang, Lang; Liu, Lu; Zhang, Miaomiao; Zhang, Linxia; Zhu, Cuisong; He, Qian; Ye, Lilin; Zhao, Chen; Li, Zejun; Xu, Jianqing; Zhang, Xiaoyan (Frontiers in Immunology, 2022)
Growing evidences supported the importance of CD8+ lung tissue resident memory T (TRM) cells in protection against respiratory viruses, exemplified by influenza A virus. However, the underlying in vivo mechanism remains largely undetermined. Here we used mouse infection models to dissect in vivo cross-protective activity of lung CD8+ TRM cells. By simultaneously interrogating transcriptional dynamics in lung CD8+ TRM cells and surrounding tissues during early course of infection, we demonstrated that lung CD8+ TRM cells react to antigen re-exposure within hours, manifested by IFN-γ upregulation, and a tissue-wide interferon-stimulated gene (ISG) program is subsequently elicited. Using antibody-mediated IFN-γ neutralization and IFN-γ receptor knockout mice, we could show that the induction of several important antiviral ISGs required IFN-γ signaling, so did the suppression of key inflammatory cytokines. Interestingly, there were also examples of ISGs unaffected in the absence of IFN-γ activity. Collectively, focusing on in situ characterization of lung CD8+ TRM during very early stage of infection, a critical period of host antiviral defense that has been poorly investigated, our studies highlight that these cells, once triggered by antigen re-exposure, are programmed to produce IFN-γ expeditiously to promote a lung-wide antiviral response for effective virus control.